HUBUNGAN KONSEP DIRI DENGAN REGULASI EMOSI ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Rahwani, Siti; Chairilsyah, Daviq; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The aims of this research is to know correlation between relationship of self-concept with the emotion regulation of children aged 5-6 years in TK Negeri Pembina 3 subdistrict Marpoyan Damai Pekanbaru city. As for the population of this research aged 5-6 years at TK Negeri Pembina 3 subdistrict Marpoyan Damai Pekanbaru city that consist of 80 children, of this research sample as many as 67 children which taken by using Slovin formula. Method of this research is pearson Product Moment Correlation. The technique of collecting data used scale test and statistic analytical by using SPSS program for windows Ver. 22. The result of hypothesis showed that there was a significant positive correlation between relationship of self-concept and emotion regulation of children aged 5-6 years in TK Negeri Pembina 3 subdistrict Marpoyan Damai Pekanbaru city. It could be seen from the result of correlation coefficient that rxy= 0,325 and significant level is0,007 < 0,05. The level of correlation between relationship of self-concept with the emotion regulation of children aged 5-6 years in TK Negeri Pembina 3 subdistrict Marpoyan Damai Pekanbaru city is in the middle category with the rank of determinan coeffisien in the amount 10,565%, it means that relationship of self-concept with the emotion regulation as much as 10,56%.Key Words: Self-concept, Emotional Regulation